Information and Communication Technologies in Education LMS Systems (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Information and communication technologies (ICT) are playing an increasingly important role in education, creating new opportunities for improving learning and sharing knowledge. One of the main components of ICT in education is educational management systems (Learning management systems, LMS).